West Bank and Gaza - Transport Sector Strategy Note - World Bank (Washington, DC, 2013)
The purpose of this Transport Sector Note (TSN) is to assist the Palestinian Authority (PA) in developing a strategy for the sector that can aid in addressing the immediate constraints and transport issues in support of the PA's effort to revive the national economy, improve mobility and reduce poverty. The TSN also aims to assist the responsible sector ministries prepare a coherent strategic framework and program for the sector. Secondary objectives are to update the Bank's knowledge of the transport sector priorities and identify priority interventions and support for the donor community s consideration. The scope of this TSN encompasses the transport infrastructure, including the road network, ports, and crossings, as well as the public transport system. After an introductory chapter, the Note includes a review of the following topics: current status of the transport sector; proposed strategic framework for development of the transport sector; and financing the proposed strategic framework.